Atrioventricular Cross-Talk Leading to Ventricular Pacing Inhibition in a Dual-Chamber ICD. (15th October 2011) - Debie, Luuk; Broers, Bernard; van Opstal, Jurren; van Gelder, Berry M.
Abstract : We report atrio-ventricular cross talk in a patient with a dual chamber ICD leading to ventricular pacing inhibition. This was observed in an ICD without the ventricular safety pace option, which normally is a sufficient protection against this phenomenon. Cross talk could be prevented effectively by reprogramming ventricular sensitivity to a less sensitive setting.